GAMBARAN POLA SIBLING RELATIONSHIP PADA ADIK USIA REMAJA DENGAN KAKAK USIA DEWASA AWAL - Veronica Lestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2017)
Sibling relationship is a relationship between siblings in one family. It is known that sibling relationship influence each sibling, especially younger sibling. Sibling with age gap can make sibling relationship less close because each sibling is at different stages of development. Furman and Buhrmester (1985) said that sibling relationship quality can be showed by four sibling relationship pattern, which are warmth, relative power, conflict, and sibling rivalry. This research aims to describe sibling relationship on adolescence who has young adult older sibling. This research is using qualitative method and purposive sampling to involve five adolescence who has young adult older sibling. The result shows that the five subjects have warmth sibling relationship pattern. Fours subjects have relative power sibling relationship pattern with some of their siblings. Two subjects have conflict sibling relationship pattern with some of their siblings. Moreover, there’s no subjects who shows sibling rivalry with their siblings.Keywords: Sibling Relationship, Age Gap, Adolescence Young Sibling